Penertiban Pedagang Kaki Lima Oleh Satuan Polisi Pamong Praja Di Jalan H.R Soebrantas Kota Pekanbaru - M. Reza Shah Pahlevi; Khairul Amri (Universitas Palangka Raya, 2024)
The unresolved problem of street vendors on H.R. Soebrantas Street is a dilemma. City planning problems and public order disturbances are always caused by the presence of street vendors. The Pekanbaru City Civil Service Police Unit, which assists the regional government in securing and enforcing regional government policies specifically in the field of public order, has often carried out enforcement for the sake of controlling, which is a supporting element for the regional government's duties. secure and implement regional government policies specifically in the field of public order. This research aims to determine the performance of the Civil Service Police Unit in controlling street vendors on Jalan H.R Soebrantas, Tampan/Binawidya District, Pekanbaru City. Apart from that, this research aims to determine and analyze the inhibiting factors in the process of controlling street vendors by the Civil Service Police Unit on Jalan H.R Soebrantas. This research uses Agus Dwiyanto's theory which uses indicators: Productivity, Service Quality, Responsiveness, Responsibility and Accountability. This research method uses qualitative methods and descriptive research which was carried out at the Pekanbaru City Civil Service Police Unit Office and on Jalan H.R Soebrantas. From the results of measurements of each sub-indicator of the research carried out, it can be stated that street vendor control activities by civil service police units have been implemented but are included in the Ineffective and Not Optimal category because there are still obstacles faced in the field, namely: lack of awareness among Street vendors understand Pekanbaru city regional regulations, lack of space to relocate traders on Jalan H.R Soebrantas, no monitoring post to supervise street vendors, and lack of facilities and infrastructure for controlling street vendors